Essays in criminal law in honour of Sir Gerald Gordon - Gordon, Gerald H.; Chalmers, James, 1976-; Leverick, Fiona; Farmer, Lindsay, 1963-; Ashworth, Andrew (Edinburgh studies in law, 2010)
A collection of essays honouring the work of Sir Gerald Gordon CBE QC LLD (1929- ). In modern times few, if any, individuals can have been as important to a single country's criminal law as Sir Gerald has been to the criminal law of Scotland. His monumental work The Criminal Law of Scotland (1967) is the foundation of modern Scottish criminal law and is recognised internationally as a major contribution to academic work on the subject. Elsewhere, he has made significant contributions as an academic, judge and as a member of the Scottish Criminal Cases Review Commission. Reflecting the academic rigour and practical application of Sir Gerald's work, this volume includes essays on criminal law theory, substantive law and evidence and procedure by practitioners and academics within and outside of Scotland, including contributions from England, Ireland and the USA. Key Features. The chapters encompass a broad range of subjects of contemporary interest and significance Analyses both substantive and procedural criminal law The contributors include practitioners and academics from both within and outwith Scotland, reflecting the influence and recognition afforded to Sir Gerald's work